2019
DOI: 10.1002/jcc.26098
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Membrane Metal Transport System: Dynamics and Energetics of mer Proteins

Abstract: The mer operon in bacteria encodes a set of proteins and enzymes that impart resistance to environmental mercury toxicity by importing Hg 2+ and reducing it to volatile Hg(0). Because the reduction occurs in the cytoplasm, mercuric ions must first be transported across the cytoplasmic membrane by one of a few known transporters. MerF is the smallest of these, containing only two transmembrane helices and two pairs of vicinal cysteines that coordinate mercuric ions. In this work, we use molecular dynamics simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…In the bacterial mercurial compounds detoxification system, organomercurial lyase (MerB) and mercuric reductase (MerA) can sequentially demethylate methylmercury (MeHg) to Hg(II) and reduce Hg(II) to Hg0, respectively [ 67 ]. Fourteen MAGs contained mer gene encoding the mercuric ion pore superfamily, which catalyze Hg(II) uptake from the periplasm, and its transport across the membrane into the cytoplasm for reduction by MerA [ 68 ]. In addition, we found that 26 MAGs contained the merB gene.…”
Section: Resultsmentioning
confidence: 99%
“…In the bacterial mercurial compounds detoxification system, organomercurial lyase (MerB) and mercuric reductase (MerA) can sequentially demethylate methylmercury (MeHg) to Hg(II) and reduce Hg(II) to Hg0, respectively [ 67 ]. Fourteen MAGs contained mer gene encoding the mercuric ion pore superfamily, which catalyze Hg(II) uptake from the periplasm, and its transport across the membrane into the cytoplasm for reduction by MerA [ 68 ]. In addition, we found that 26 MAGs contained the merB gene.…”
Section: Resultsmentioning
confidence: 99%
“…1A), which together enable the bacterium to promptly respond to the mercury stress (Zheng et al ., 2018). Within the mer operon, the smallest of the mercury transporters, MerF has a molecular mass of only 8.7 kDa and consists solely of a simple helix‐loop‐helix domain with two pairs of cysteine residues for binding Hg 2+ (Hwang et al ., 2020), and it is the homologue of MerT, another reported Hg 2+ transporter (Sone et al ., 2013). However, combining our previous report (Zheng et al ., 2018) and the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These genes provide plants with the ability to gather more Hg in their tissues than wild type. The merP encodes a periplasmic protein that facilitates the absorption of Hg 2+ and is physically linked to merT (Hwang et al, 2020).…”
Section: Phytoremediationmentioning
confidence: 99%